Acceptability and Willingness-to-Pay for a Hypothetical Ebola Virus Vaccine in Nigeria. - Maduka Donatus Ughasoro; Dorothy Omono Esangbedo; Beckie Nnenna Tagbo; Ijeoma Chigozie Mejeha (Public Library of Science (PLoS), 2015)
BACKGROUND:Ebola virus disease is a highly virulent and transmissible disease. The largest recorded fatality from Ebola virus disease epidemic is ongoing in a few countries in West Africa, and this poses a health risk to the entire population of the world because arresting the transmission has been challenging. Vaccination is considered a key intervention that is capable of arresting further spread of the disease and preventing future outbreak. However, no vaccine has yet been approved for public use, although various recombinant vaccines are undergoing trials and approval for public use is imminent. Therefore, this study aimed to determine the acceptability of and willingness-to-pay for Ebola virus vaccine by the public. METHODS:The study was a community-based cross-sectional qualitative and quantitative interventional study conducted in two communities, each in two states in Nigeria. An interviewer-administered questionnaire was used to collect information on respondents' knowledge of the Ebola virus, the ways to prevent the disease, and their preventive practices, as well as their acceptability of and willingness-to-pay for a hypothetical vaccine against Ebola virus disease. The association between acceptability of the vaccine and other independent variables were evaluated using multivariate regression analysis. RESULTS:Ebola virus disease was considered to be a very serious disease by 38.5% of the 582 respondents (224/582), prior to receiving health education on Ebola virus and its vaccine. Eighty percent (80%) accepted to be vaccinated with Ebola vaccine. However, among those that accepted to be vaccinated, most would only accept after observing the outcome on others who have received the vaccine. More than 87.5% was willing to pay for the vaccine, although 55.2% was of the opinion that the vaccine should be provided free of charge. CONCLUSION:The level of acceptability of Ebola virus vaccine among respondents was impressive (though conditional), as well as their willingness to pay for it if the vaccine is not publicly funded. In order to achieve a high uptake of the vaccine, information and education on the vaccine should be extensively shared with the public prior to the introduction of the vaccine, and the vaccine should be provided free of charge by government.